POSTOPERATIVE ACUTE KIDNEY INJURY IN CARDIOVASCULAR SURGERY: A STUDY FROM A NIGERIAN HIGH DEPENDENCY CENTER - Uduagbamen , O; Osanusi, Michael A (International Journal of Contemporary Health Sciences and Technology, 2025)
Acute kidney injury (AKI) is a common complication in surgical procedures, particularly heart and vascular surgeries, leading to increased healthcare costs, prolonged hospital stays, and adverse outcomes. Various criteria and definitions have been used to diagnose AKI, with the kidney disease: Improving Global Outcome (KDIGO) criteria being the most widely accepted. Cardiac surgery-associated AKI (CSA-AKI) has a reported prevalence of approximately 30%, while the prevalence of AKI requiring dialysis (AKI-D) is around 6%. Accurate and timely diagnosis of CSA-AKI is crucial for early intervention and improved patient outcomes.